Science Laboratory Management and the Implications for Students’ Motivation and Learning Achievement - Wasitoh, Evi; Ismaya, Bambang; Abduloh; Suryaman, Maman (Research Horizon, 2025)
The management of science laboratories plays a strategic role in supporting experiment-based learning, which can enhance students’ motivation and academic achievement. However, many schools still face challenges related to limited equipment, inadequate maintenance, and the inconsistent implementation of laboratory activities. This study aims to explore in depth how science laboratories are managed in secondary schools and how such management influences students’ motivation and academic performance. A qualitative approach with a case study design was employed. Data were collected through observations, in-depth interviews with teachers, students, and laboratory personnel, and document analysis, including inventory records, practicum schedules, and laboratory SOPs. Data analysis followed Miles, Huberman, and Saldaña’s interactive model. The findings indicate that the laboratory management is functional but not optimal due to limited resources, the absence of laboratory assistants, and irregular practicum implementation. Both teachers and students express highly positive perceptions of laboratory activities, which are shown to significantly increase motivation through engaging and meaningful hands-on experiences. The results also reveal that students who actively participate in laboratory work demonstrate better conceptual understanding and higher academic achievement. The study concludes that science laboratories have substantial potential as pedagogical spaces that mediate improvements in motivation and learning outcomes.